Immune Responses Against West Nile Virus and Mosquito Salivary Proteins in Wild Birds from St. Tammany Parish, Louisiana - Alyssa R. Schwinn; Sara Harris; Zoe Jacobs; Jane de Verges; Samuel B. Jameson; Dawn M. Wesson; Sarah R. Michaels; Kevin A. Caillouët; Berlin Londoño-Renteria (Zoonotic Diseases)
Though a variety of methods are used to conduct West Nile virus (WNV) surveillance, accurate prediction and prevention of outbreaks remain a global challenge. Previous studies have established that the concentration of antibodies to mosquito saliva is directly related to the intensity of exposure to mosquito bites and can be a good proxy to determine risk of infection in human populations. To assess exposure characteristics and transmission dynamics among avian communities, we tested the levels of IgY antibodies against whole salivary glands of Aedes albopictus and Culex quinquefasciatus, as well as WNV antigen, in 300 Northern cardinals sampled from April 2019 to October 2019 in St. Tammany Parish, Louisiana. Though there were no significant differences in antibody responses among sex or age groups, exposure to Ae. albopictus bites was more positively associated with exposure to WNV compared with Cx. quinquefasciatus exposure (ρ = 0.2525, p < 0.001; ρ = 0.1752, p = 0.02437). This association was more pronounced among female birds (ρ = 0.3004, p = 0.0075), while no significant relationship existed between exposure to either mosquito vector and WNV among male birds in the study. In general, two seasonal trends in exposure were found, noting that exposure to Ae. albopictus becomes less intense throughout the season (ρ = −0.1529, p = 0.04984), while recaptured birds in the study were found to have increased exposure to Cx. quinquefasciatus by the end of the season (ρ = 0.277, p = 0.0468). Additionally, we report the identification of several immunogenic salivary proteins, including D7 family proteins, from both mosquito vectors among the birds. Our results suggest that Ae. albopictus may have a role in early-season transmission of WNV, particularly among brooding females and hatchling cardinals. However, bloodmeal analysis was not included in this work and further studies are needed to verify this assumption. Yet, broad circulation of WNV in nesting avian communities could enhance risk of infection among Cx. quinquefasciatus mosquitoes in the late season, with the potential to contribute to human disease incidence and epizootic spillover in the environment.